2014
DOI: 10.1124/mol.114.092544
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Epigenetic Regulation of 14-3-3σ Expression in Acquired Gemcitabine Resistance by Uhrf1 and DNA Methyltransferase 1

Abstract: Although gemcitabine is the most commonly used drug for treating pancreatic cancers, acquired gemcitabine resistance in a substantial number of patients appears to hinder its effectiveness in successful treatment of this dreadful disease. To understand acquired gemcitabine resistance, we generated a gemcitabineresistant pancreatic cancer cell line using stepwise selection and found that, in addition to the known mechanisms of upregulated expression of ribonucleotide reductase, 14-3-3s expression is dramaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…As shown in Figure 4A–B, BxPC-3/Sh-σ had reduced while MiaPaCa-2/σ had increased levels of PARP1 protein and mRNA compared with their respective control cells. Transient 14-3-3σ knockdown in BxPC-3 cells using two different shRNAs or a siRNA pool as describe previously (4) also successfully reduced PARP1 expression (Figure 4C). …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…As shown in Figure 4A–B, BxPC-3/Sh-σ had reduced while MiaPaCa-2/σ had increased levels of PARP1 protein and mRNA compared with their respective control cells. Transient 14-3-3σ knockdown in BxPC-3 cells using two different shRNAs or a siRNA pool as describe previously (4) also successfully reduced PARP1 expression (Figure 4C). …”
Section: Resultssupporting
confidence: 73%
“…Cell lysate preparation, Western blot analyses, and immunoprecipitation were performed as previously described (4,18). Briefly, cultured cells were harvested, washed with chilled PBS 3 times, and lysed in TNN lysis buffer (50 mM Tris-HCl, pH 7.5, 150 mM NaCl, 0.5% Nonidet P-40, 50 mM NaF, 1 mM Na 3 VO 4 , 1 mM DTT, 0.1% SDS, and 2 mM PMSF) for 30 minutes on ice with agitation.…”
Section: Methodsmentioning
confidence: 99%
“…It interacts, among many others, with DNA methyltransferases (DNMTs), proliferating cell nuclear antigen (PCNA), histone deacetylase 1 (HDAC1), ubiquitin specific protease 7 (USP7), euchromatic histone-lysine N methyltransferase 2 (G9a/EHMT2) and Tat Interacting Protein 60 (Tip60) to maintain DNA methylation patterns and histone epigenetic marks in various physiological and pathological conditions [ 18 , 19 , 37 42 ]. Together with its partners, UHRF1 ensures the regulation, through “silencing” of a high number of tumor suppressor genes and long non-coding RNAs, including RB1 [ 43 ], p16 ( CDKN2A) [ 44 – 48 ], CDH13 and SHP1 [ 49 ], SOCS3 and 3OST2 [ 50 ], BRCA1 [ 51 ], CDX2, RUNX3, FOXO4, PPARG and PML [ 52 , 53 ], MEG3 [ 54 ] and 14-3-3σ [ 55 ]. Moreover, KISS1 , functioning as a metastasis suppressor in various cancers, also looks to be under the control of UHRF1 [ 56 ].…”
Section: The Epigenetic Integrator Uhrf1mentioning
confidence: 99%
“…It has also been shown previously that increased 14-3-3σ expression associates with poor prognosis of PDAC [ 6 , 7 ]. Recently, using a newly established gemcitabine resistant PDAC cell line, G3K derived from MiaPaCa-2 cells via stepwise gemcitabine selections, we showed that 14-3-3σ expression is upregulated via epigenetic regulation and contributes to the acquired gemcitabine resistance in the gemcitabine-selected PDAC G3K cells [ 8 ]. In addition to the acquired gemcitabine resistance in PDAC cells, 14-3-3σ has been implicated in acquired doxorubicin resistance in breast cancer cells [ 9 ] and in cisplatin resistance of colon cancer cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%